P200 The clinical, utility and economic benefits of securing minimal important difference in asthma control test using a novel tool: the a.b.o.v.e. asthma (achieving-better-outcomes-and-value-for- everybody-in-asthma). (15th November 2017) - Manfrin, A; Tinelli, M
Abstract : Introduction and Objectives: Asthma accounts for an economic loss of €72 billion annually in the 28 countries of the European Union with a monetised value of DALYs cost of €38 billion. One of the key priorities in asthma management is achieving asthma control. It is crucial to understand whether providing a minimally clinical important difference (MID) of the asthma control test (ACT) score can bring better clinical, utility and economic outcomes. Aim: To test whether the A.B.O.V.E. ASTHMA (Achieving-Better-Outcomes-and-Value-for-Everybody-in-Asthma) tool works in terms of securing the MID in ACT and, in doing so, we can provide positive outcomes for patients, payers, providers and policy makers. Methods: Using the data obtained from the Italian Medicines Use Review (I-MUR) cluster randomised controlled trial (C-RCT; 2014–2015) involving 1263 asthma patients and 283 pharmacists in Italy, we tested whether A.B.O.V.E. ASTHMA was able to (1) link a clinical outcome (ACT score) to economic and utility dimensions; (2) secure a MID improvement in ACT and the outcomes attached in terms of cost savings for the healthcare provider and gains in health utility (% of being in perfect health). Results: Data from the C-RCT showed that after receiving the A.B.O.V.E. ASTHMA intervention, patients improved their asthma control, assessed by the ACT, shifting from not controlled (RED) towards partially controlled (YELLOW), and fully controlled (GREEN) groups. Asthma control improved in the vast majority of patients (median ACT score was 19 at baseline, 20 at 3 month and 21 at 6 month post intervention). The number of patients who were on MID target and reached the GREEN group at 3 and 6 months were 129 (15.8%) and 162 (19.9%) respectively. The overall annual cost savings per 1000 patients attached to the shift towards the MID target was equal to: 3 46 012 euros (NHS) at 3 months and increased to 4 25 483 euros (NHS) at 6 months (see Table ). Health utility gains were equal to 0.9 and 0.29 years in full health, respectively. Conclusions: The A.B.O.V.E. ASTHMA tool can secure MID in ATC and, in doing so, better outcomes in terms of clinical, utility and economic results. The calculation of the cost-saving for the NHS was estimated for a population of 1000 asthma patients